2007
DOI: 10.1002/asi.20639
|View full text |Cite
|
Sign up to set email alerts
|

Tracking open access journals evolution: Some considerations in open access data collection validation

Abstract: This article examines the evolution of a collection of open access journals (OAJs,) indexed by the Science Citation Index (SCI; Thomson Scientific Philadelphia, PA) against four validity criteria including a free, immediate, full and constant access policy for at least 5 years. Few journals are found to be wrongly identified as OAJ or to have a dubious access policy. Some delayed journals evolved into gold OA; however, these are scarce compared to the number of journals that withdrew from gold OA to be an emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
(9 reference statements)
0
20
1
Order By: Relevance
“…1 The identification and validation methods and rationale for the selection of the journals are respectively described in SOTUDEH & HORRI [2007A;2007B] and are described here in brief.…”
Section: Methodsmentioning
confidence: 99%
“…1 The identification and validation methods and rationale for the selection of the journals are respectively described in SOTUDEH & HORRI [2007A;2007B] and are described here in brief.…”
Section: Methodsmentioning
confidence: 99%
“…3 For the statistical analyses it is essential to select a discipline with a relatively high number of OAJs. A considerable number of OAJs convert into non-OAJs (Sotudeh & Horri, 2007b), however, as the development over time is not the focus in this study it is sufficient that the journal had OA status at the time of data collection. An overview of the included journals and some of their characteristics is provided in appendix 1-3.…”
Section: Methodsmentioning
confidence: 99%
“…One hundred thirty-nine gold OAJs, indexed by SCI, were identified and validated in terms of their stability in providing a full, immediate, OA policy, according to the methodology described in Sotudeh and Horri (2007). In the present study, further filtering was required to homogenize the collection regarding scientific prestige.…”
Section: Journal Identification and Validationmentioning
confidence: 99%
“…As a newly established iconoclastic phenomenon, they encounter many challenges and perils causing them to be somewhat unstable and consequently giving rise to probable fluctuations in their performance. In a recent article, Sotudeh & Horri (2007) concentrating on the evolution of gold OAJs, showed that OAJs indexed by SCI (Science Citation Index; Thomson Scientific, Philadelphia, PA) not only reached the highest number that has ever been reported, but also a majority of them have been actively following a consistent, immediate, full-access policy.…”
Section: Introductionmentioning
confidence: 98%